MENINGKATKAN KEMAMPUAN OPERASI HITUNG PENJUMLAHAN DENGAN PEMBELAJARAN MATEMATIKA REALISTIK PADA ANAK TUNAGRAHITA SEDANG - Hendra - Jhoni (Universitas Negeri Padang, 2012)
This study begins with the observation that researchers do in the SDLB N 40 Koto Baru Solok. Researchers found that a child is experiencing problems on mentally and we called with´’tunagrahita’’ in math especially arithmetic operations of addition, this study aimed to calculate the sum of operating ability in children with learning mathematics can raising Realistic. This study used experimental approach in a Single Subject Risearch (SSR) with a research design using design A - B - A. The subject of this study was a child Tunagrahita being. Target behavior is raising the sum of the arithmetic operation of said operation of calculating the sum total of about ten questions on the student worksheet.